Economic Partnership Agreements between the EU and the African, Caribbean and Pacific group of states: Status of negotiations, conflicts, resolutions - Bettina Rudloff; Clara Weinhardt (Stiftung Wissenschaft und Politik (SWP), 2011)
It appears that the EU's negotiations over Economic Partnership Agreements between the EU and seven regional groups, which together comprise 79 African, Caribbean and Pacific states (the so-called ACP states), have arrived at a stalemate. Thus far it has only been possible to conclude an agreement with one group, including all its members. Negotiations with other groups have only resulted in transitional agreements with individual states or sub-groups of states. The EU deplores the negative attitude among its negotiating partners and defends the agreements as instruments of economic development. But do these agreements present the ACP side with sufficient advantages so that it will engage in reaching a conclusion? Can tailor-made agreements be arranged so that the various interest groups are better taken into account?
Keywords: 320